Root uptake of Cs-137 by natural grasses as a function of properties of soils - Osores, José (2010)
This work studies the dependence of Cs-137 root uptake on the structure of landscape, especially on the properties of soils, under controlled conditions. Researches were carried out at various levels of Cs-137 contamination (from 20 up 1000 kBq/m²), with five different types of soils, which differ in texture and granulometric composition. The results showed that transfer factor (TF) values of Cs-137 differ 5 times for the natural grassy coenoses. The correlation between Cs-137 TF values and granulometric composition of soil was determined for both automorphic and hydromorphic mineral soils.